A Framework to Assist School Psychologists and Counsellors in Recommending Quality Apps for Supporting Diabetes Self-Management: An Illustrative Assessment Using Content Analysis. Issue 1 (3rd October 2018) - Furlonger, Brett; Ostojic, Marko; Chung, Jasmine; Philips, Katrina; Busacca, Margherita; Moore, Dennis; Anderson, Angelika
Abstract : A framework was examined to assist school psychologists and counsellors in recommending quality apps for supporting diabetes self-management. A content analysis was undertaken to assess behaviour change strategies in Apple and Android smartphone apps for the self-management of type 2 diabetes. The Behaviour Change Technique Taxonomy was used to assess the presence of behaviour change strategies, while the Mobile App Rating Scale was used to assess overall app quality. Raters found, on average, 7.13 behaviour change techniques out of a possible 93, indicating few behaviour change techniques in apps for the self-management of Type 2 diabetes. Analysis indicated that apps of a higher overall quality tended to incorporate more behaviour change strategies. It was concluded that mental-health professionals are advantaged if they are able to assess and refine selection tools for matching apps with the needs of students with diabetes.